Laparoscopic management of a cornual pregnancy following failed methotrexate treatment: case report and review of literature. (2nd August 2020) - Tinelli, Raffaele; Stomati, Massimo; Surico, Daniela; Cicinelli, Ettore; Trojano, Giuseppe; Angioni, Stefano
Abstract: To describe a rare case of a singleton 8-week cornual pregnancy (CP), treated by laparoscopic incision of the uterine wall, the ectopic pregnancy was removed and the uterine site was sutured with interrupted sutures. A 21-year-old woman was admitted for suspected singleton CP at week 8. Clinical examination, b-hCG increase, and transvaginal ultrasonography (TU) were used to monitor the suspected diagnosis of an ectopic pregnancy. Following failure of methotrexate administration, surgeons performed a laparoscopy. The CP removal was performed by laparoscopic incision, enucleating the corneal mass and suturing the uterine site of the ectopic pregnancy with interrupted sutures. Intraoperative and postoperative complications and uterine integrity preservation were studied. Postoperative recovery period was normal, without intraprocedural or postprocedural complications.Uterine integrity was preserved. No further therapeutic interventions were needed in follow-up. This study confirmed the feasibility, safety and efficacy of performing a safe, minimally invasive, laparoscopic treatment of an early unruptured CP, without intraoperative and postoperative complications, with a normal postoperative recovery period and preservation of uterine integrity.